PENGARUH PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP KINERJA PERUSAHAAN PADA SUBSEKTOR ASURANSI YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Windy Artika Sipayung; Marthinus Ismail (Jurnal Ekonomis, 2021)
The effect of determined taxes and Tax planning on company performance on insurance subsectors listed on the indonesia stock excange, 2017-2019. The research sample consisted of 16 companies and thus there were 48 samples. This study aims to determine whether the variable deferred tax and tax planning affect the company's performance in the insurance subsector. This study uses purposive sampling to determine the sample under study. Several methods of data analysis will be processed, with descriptive analysis, hypothesis testing, and regression analysis to provide conclusions. The data analysis method used is multiple linear regression. The results of this study indicate that deferred tax affects company performance while tax planning does not affect company performance